2012
DOI: 10.1093/jmcb/mjs025
|View full text |Cite
|
Sign up to set email alerts
|

Age- and diet-dependent requirement of DJ-1 for glucose homeostasis in mice with implications for human type 2 diabetes

Abstract: Elderly patients often suffer from multiple age-related diseases. Here we show that the expression of DJ-1, an antioxidant protein with reduced expression in the central nervous system of patients with Parkinson's disease, is reduced in pancreatic islets of patients with type 2 diabetes mellitus (T2DM). In contrast, under non-diabetic conditions, DJ-1 expression increases in mouse and human islets during aging. In mouse islets, we show that DJ-1 prevents an increase in reactive oxygen species levels as the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 62 publications
6
81
1
Order By: Relevance
“…Our data indicated that impaired Nrf2 activation could potentially be attributed to reduced DJ-1 induced Nrf2 stabilization and increased Nrf2 nuclear export via GSK-3β. Similar findings of reduced DJ-1 expression have been reported in Type-II diabetic mouse models or cell lines [123,124], with a marked correlation between altered lipid metabolism and DJ-1 expression in both rodents and humans [125,126]. In most age-related diabetic pathologies (as well as other Nrf2-related disease pathologies such as cancer), alterations in Nrf2 activation have been strongly linked with Keap1 promoter demethylation [127][128][129][130] as opposed to enhanced DJ-1 methylation [122].…”
Section: Epigenetic Nrf2 Priming Mechanisms In Diabetessupporting
confidence: 86%
“…Our data indicated that impaired Nrf2 activation could potentially be attributed to reduced DJ-1 induced Nrf2 stabilization and increased Nrf2 nuclear export via GSK-3β. Similar findings of reduced DJ-1 expression have been reported in Type-II diabetic mouse models or cell lines [123,124], with a marked correlation between altered lipid metabolism and DJ-1 expression in both rodents and humans [125,126]. In most age-related diabetic pathologies (as well as other Nrf2-related disease pathologies such as cancer), alterations in Nrf2 activation have been strongly linked with Keap1 promoter demethylation [127][128][129][130] as opposed to enhanced DJ-1 methylation [122].…”
Section: Epigenetic Nrf2 Priming Mechanisms In Diabetessupporting
confidence: 86%
“…In fact, some studies have shown that with the ascending of blood glucose, the content of DJ-1 was increased to inhibit the expression of ROS. 27,28 . In addition, the renal protective effects in diabetic rats might be enhanced by the activation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Its mutations have been linked to familial forms of Parkinson disease (40,41). Park7 expression is reduced in pancreatic islets of type 2 diabetic patients, where it may be required for mitochondrial function and glucosestimulated insulin secretion (42). Cerebrospinal, but not plasma, Park7 levels have been proposed as a biomarker of Parkinson disease (43,44), whereas 4-hydroxy-2-nonenal-modified Park7 could be a plasma biomarker of late-stage Parkinson (45).…”
Section: Discussionmentioning
confidence: 99%